Music Preferences and Language Anxiety among Introverted and Extroverted EFL Students - Suta, I Putu Wirya; Setiyadi, Ag. Bambang; Mahpul, Mahpul (Jurnal Pendidikan Bahasa Inggris undiksha, 2025)
Language anxiety has been recognized as a significant impediment to effective language acquisition, and music may affect this anxiety. This research investigates the correlation between musical tastes and language anxiety in introverted and extroverted EFL students. Data were acquired from 46 students using surveys utilizing a quantitative design. The Eysenck Personality Inventory (EPI) classified participants as introverts or extroverts, while an adapted Foreign Language Classroom Anxiety Scale (FLCAS) assessed language anxiety. The Study of Music Preferences (STOMP) questionnaire was employed to ascertain their favored music genres. SPSS was employed to analyze the data and investigate the correlation between musical preferences and language anxiety among introverted and extroverted students. The results demonstrate that both introverts and extroverts favor "Upbeat & Conventional" music, with no statistically significant relationship between personality traits and music preferences (p = 0.496). Moreover, whereas introverts displayed greater language anxiety than extroverts, this disparity was not statistically significant (p = 0.312). Additionally, the findings regarding musical preferences and anxiety levels suggest that while students may prefer certain genres, these choices do not significantly affect the anxiety encountered during language learning activities (p = 0.388). The research highlights the intricate interplay among personality, music, and anxiety, indicating that elements outside personality features may affect musical preferences and anxiety levels. The findings underscore the necessity of establishing supportive educational settings customized to individual requirements to improve language acquisition and alleviate anxiety. Additional investigation is advised to examine the intricate relationships among these variables.